A Recombinant BCG Vaccine Is Safe and Immunogenic in Neonatal Calves and Reduces the Clinical Disease Caused by the Respiratory Syncytial Virus - Díaz, Fabián E.; Guerra-Maupome, Mariana; McDonald, Paiton O.; Rivera-Pérez, Daniela; Kalergis, Alexis M.; McGill, Jodi L. (Frontiers in Immunology, 2021)
The human respiratory syncytial virus (hRSV) constitutes a major health burden, causing millions of hospitalizations in children under five years old worldwide due to acute lower respiratory tract infections. Despite decades of research, licensed vaccines to prevent hRSV are not available. Development of vaccines against hRSV targeting young infants requires ruling out potential vaccine-enhanced disease presentations. To achieve this goal, vaccine testing in proper animal models is essential. A recombinant BCG vaccine that expresses the Nucleoprotein of hRSV (rBCG-N-hRSV) protects mice against hRSV infection, eliciting humoral and cellular immune protection. Further, this vaccine was shown to be safe and immunogenic in human adult volunteers. Here, we evaluated the safety, immunogenicity, and protective efficacy of the rBCG-N-hRSV vaccine in a neonatal bovine RSV calf infection model. Newborn, colostrum-replete Holstein calves were either vaccinated with rBCG-N-hRSV, WT-BCG, or left unvaccinated, and then inoculated via aerosol challenge with bRSV strain 375. Vaccination with rBCG-N-hRSV was safe and well-tolerated, with no systemic adverse effects. There was no evidence of vaccine-enhanced disease following bRSV challenge of rBCG-N-hRSV vaccinated animals, suggesting that the vaccine is safe for use in neonates. Vaccination increased virus-specific IgA and virus-neutralization activity in nasal fluid and increased the proliferation of virus- and BCG-specific CD4+ and CD8+ T cells in PBMCs and lymph nodes at 7dpi. Furthermore, rBCG-N-hRSV vaccinated calves developed reduced clinical disease as compared to unvaccinated control calves, although neither pathology nor viral burden were significantly reduced in the lungs. These results suggest that the rBCG-N-hRSV vaccine is safe in neonatal calves and induces protective humoral and cellular immunity against this respiratory virus. These data from a newborn animal model provide further support to the notion that this vaccine approach could be considered as a candidate for infant immunization against RSV.